Perceptions of Indonesian College Students about Offline and Online TOEFL ITP Preparation Class - Damanik, Juli Yanti; Pasaribu, Monalisa (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
Due to college students’ mobility nowadays (e.g. joining Merdeka Belajar Kampus Merdeka program) that allows students to be off campus for a time, some learning processes have to be conducted online. The objective of this study was to investigate how students at an Indonesian college perceived the conduct of online and offline TOEFL ITP preparation classes. Participants in this study were 47 students at an Indonesian private college who completed the TOEFL ITP preparation course. Data collection and data analysis were designed with a mixed-method approach. An online questionnaire with closed and open-ended questions was administered for data collection. The framework used in this study was the Community of Inquiry (CoI). The data obtained was analyzed by practicing qualitative and quantitative approaches as well to gain the participants’ deeper insights into the issue. The participants believed that social, cognitive, and teaching presence could be established in both face-to-face and online learning settings despite their higher preference for offline classes, especially in social presence. Furthermore, it was known that the participants’ preference for teaching methods was in line with the methodology that their instructors carried out. The matter was in the different instructions that they had during online and offline sessions. Implications for teachers are to make sure the learning process can be conducted by establishing a social presence, cognitive presence, and teaching presence.